The Influence of Performance Expectations on The Behavior of Sharia Share Users: The Utaut Model - Hurian Kamela (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2023)
There is still limited research on sharia shares related to the behavior of the UTAUT method (individuals). The aim of this research is to measure Muslims' opinions about sharia to consider sharia instruments (sharia shares) and use them as long-term investments. The reason for conducting this research is because of society's limitations regarding technological development and knowledge, so it is necessary to measure knowledge, because public knowledge about investment is mainly in the form of savings, without paying attention to diversification with other financial instruments. (for example, conventional or sharia shares. The dependent variable is performance expectations . The method used is a regression (quantitative) questionnaire of 50 people. The result is that there is public interest in buying sharia shares, especially for respondents who have master's degrees in education, because the sample size is the largest (35 people) are graduates. This can happen because the higher the education, the more likely they are to take risks on sharia stocks.